2017
DOI: 10.1080/24750573.2017.1293239
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of repetitive transcranial magnetic stimulation for treatment-resistant major depression and the impact of anxiety symptoms on outcome

Abstract: Objective: The aim of this study was to evaluate the efficacy of repetitive transcranial magnetic stimulation (rTMS) in patients with treatment-resistant major depression and to explore the relationship between the outcome and comorbid anxiety symptoms. Methods: The study was performed on 36 patients with treatment-resistant major depression. Patients received 15 rTMS sessions to their left dorsolateral prefrontal cortex with 110% motor threshold intensity, 20 Hz frequency, and 1000 pulses per day over a three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…Our findings are in keeping with the earlier, smaller studies that have found rTMS to be effective in treating comorbid anxiety occurring in MDD (Berlim, McGirr, et al, 2011;Diefenbach et al, 2013;Durmaz et al, 2017;Greenberg et al, 1997;Kedzior et al, 2015). Our results suggest that RLF rTMS, LHF rTMS, and BL rTMS are all equally effective.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our findings are in keeping with the earlier, smaller studies that have found rTMS to be effective in treating comorbid anxiety occurring in MDD (Berlim, McGirr, et al, 2011;Diefenbach et al, 2013;Durmaz et al, 2017;Greenberg et al, 1997;Kedzior et al, 2015). Our results suggest that RLF rTMS, LHF rTMS, and BL rTMS are all equally effective.…”
Section: Discussionsupporting
confidence: 91%
“…In another openlabel study, 15 chronically depressed, severely treatment-resistant patients were treated with 20 sessions of LHF rTMS (Berlim, McGirr, Beaulieu, & Turecki, 2011), resulting in 25% and 18.3% reductions across two anxiety symptomatology rating scales. A third open-label trial of 36 depressed patients reported 15 sessions of left-sided 20 Hz rTMS resulted in large therapeutic effect sizes (Pearson's r > 0.5) on both anxiety and depression symptoms (Durmaz, Ebrinc, Ates, & Algul, 2017). Contrary to these positive findings, however, there have also been reports of worsening anxiety associated with rTMS treatment (Greenberg, McCann, Benjamin, & Murphy, 1997).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…J, 20184129 rTMSBorderlineRCTRight DLPFC + left DLPFC155 Hz or 1 Hz900 or 1500100% of RMTHRSATo evaluateclinical improvement in patients with BPD after application of rTMSHAM-A scores reduced after rTMS treatment. Both protocols produced global improvement in severity and symptoms of BPD, particularly in impulsiveness, affective instability, and angerNRYesDurmaz O, 20174236 rTMSMDDOpen-labelLeft DLPFC1520 Hz1000110% of RMTHRSATo evaluate the efficacy of rTMS in patients with treatment-resistant major depressionThe findings suggested that comorbid anxiety symptoms, particularly somatic anxiety, could predict the response to rTMS in treatment-resistant major depressive disorderHeadache in eight patients, dizziness in four patients, and lacrimation in three patients. Only one patient dropped out of the study due to side effects or intoleranceYesNoh TS, 20174317 rTMSTinnitusRCTLeft auditory cortex (AC) and left DLPFC or only the left DLPFC41 Hz2000 or 3000110% of RMTSTAIWe evaluated treatment outcomes following single-site rTMS in the DLPFC and dual-siterTMS in the AC and DLPFCGroup 1 exhibited significant improvements in scores on the STAI for both state anxiety and trait anxiety at 12 weeks posttreatment.Group 2 showed an improvement in only the STAI-X2 score at 12 weeks posttreatment.NRNoTovar-Perdomo S, 20174424 rTMSMDDOpen-label, pilot studyLeft DLPFC2010 Hz3000120% of RMTBAITo explore the effects of a course of accelerated high-frequency rTMS on two neurocognitive domains in patients with MDDDepression and anxiety scores significantly improved from pre-post HF-rTMS treatment.The absence of practice effects in our longitudinal design rai...…”
Section: Resultsmentioning
confidence: 99%
“…Pirmoradi et al observed that multiple TMS reduced cognitive and physical symptoms, pessimism, and feelings of worthlessness in patients with depression (18). According to another study performed by Durmaz et al, multiple rTMS decreased the symptoms of depression and anxiety (19). The effectiveness of multiple magnetic stimulations of the brain in working memory and depression is also confirmed by some studies (20,21).…”
Section: Introductionmentioning
confidence: 78%